People's Republic of China-Hong Kong Special Administrative Region : 2009 Article IV Consultation-Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation highlights that Hong Kong Special Administrative Region's economy was severely affected by the global financial crisis. The recovery is now under way, fueled by growth on the Mainland, supportive policies, and accommodative monetary conditions imported from the United States. Despite the steepness of the downturn in early 2009, job losses have been relatively modest and unemployment now stands at 5.2 percent. Executive Directors have welcomed the robustness of the Hong Kong banking system, the result of banks' careful risk management, and the authorities' vigilant, prudent regulation and enforcement.